An Expression of Pain or An Expression of Love?: An Analysis of Conceptual Metaphors of Grief on Medium Digital Platform - Dian Salsabilla; Qanitah Masykuroh (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to identify the types of conceptual metaphors that appear in grief narratives on the Medium.com platform and to explain how these metaphors represent the grief experiences of the authors.Methodology: This qualitative study deploys content analysis. The data consist of all sentences containing metaphorical expressions about grief collected through documentation. Ten narratives on the theme of grief published on the Medium.com platform were selected as the source of data. The data were analysed using Metaphor Identification Procedure (MIP) by the Pragglejaz Group (2007). Results: The results show two types of metaphor in stories i.e., ontological metaphors, which are more dominant, and structural metaphors. Moreover, the metaphor embraces various representations such as grief as a burden, ocean, physical strength, wild animal, or self-disintegration. Structural metaphors also appear, especially those that describe grief as physical pain and an expression of love. Overall, metaphors function as cognitive tools that help writers organize, understand, and express complex experiences of grief that are difficult to describe literally. Applications/Originality/Value: This study contributes to the development of metaphor studies in emotional discourse. Further research is recommended to expand the data corpus, compare across cultures or languages, and explore the use of metaphors in the context of grief therapy.